Industrial training for library & information science students : A Malaysian experience - Sinnasamy, Janaki; N.N. , Edzan (Persatuan Pustakawan Malaysia, 2015)
Library profession is specialized and technical in nature, and so industrial training for the library science students must have both the elements of theory and practical skills incorporated. This is becoming more pertinent with the frequent debate lately as to the relevance of libraries in the wake of emerging web technologies. We are at a crossroad in time, when even ALA seems to have difficulty defining librarianship adequately. In Malaysia, four public universities run this program, two for undergraduates and two for postgraduate programs. The industrial training is partly based on the internship model where students undergo training from one to three months. This paper will present students’ comments as well trainers’ feedback of a training program for LIS students in a public university in Malaysia. A few challenges such as unsynchronized training schedules between school and industry, and varying library systems are identified which calls for more collaborative efforts between library schools and industrial trainers.